Tetramycin ameliorates tebuconazole·azoxystrobin to control leaf spot and viral diseases of Taizishen - Bing Tian; Bing Tian; Chenglin Tang; Jiaqi Liu; Boya Jin; Cheng Zhang (Frontiers in Plant Science)
Leaf spot and viral diseases are the most frequently occurring leaf problems in Taizishen production. In this study, we examined the controlling role played by the co-application of tetramycin and low dose tebuconazole·azoxystrobin against leaf spot and viral diseases in Taizishen, investigating its resistance, electrophysiological information, growth and quality. Among them, electrophysiological information indicators include electrical signals [intrinsic capacitance (IC), resistance (IR), impedance (IZ), capacitive reactance (IXc), and inductive reactance (IXL)], intracellular water metabolism, nutrient transport, and plant metabolic activity. The results indicate that 0.3% tetramycin 1000-time + 75% tebuconazole·azoxystrobin 2000-time diluent controlled leaf spot and viral diseases the best, with protection effects of 90.03%~90.46% and 71.67%~73.08% at 15~30 days after the last fungicide application, respectively. These values are obviously higher than those treated with high doses of tetramycin or tebuconazole·azoxystrobin alone. Concurrently, their combined application could notably enhance total soluble flavonoids, total soluble phenols, protective enzyme activity, IC, intracellular water metabolism, nutrient transport, and metabolic activity, while reducing its MDA, IR, IZ, IXc, and IXL. Moreover, their co-application also could obviously ameliorate photosynthesis, biomass, agronomic trait, and root growth and quality, as well as actually reduce tebuconazole·azoxystrobin input. Additionally, the control effects of leaf spot and viral diseases in Taizishen treated by their combined application exhibited significant correlations with its disease resistance, electrophysiology, photosynthesis, growth, and quality parameters. This study highlights the combined application of low-dosage tebuconazole·azoxystrobin and tetramycin as a practicable measure for controlling leaf spot and viral diseases in Taizishen, promoting its resistance, growth, and quality, as well as reducing chemical pesticide application.